The utility of 64-multidetector computed tomography in the diagnosis and staging of hepatoblastoma patients - Moustafa Abdel Kader; Mohamed G. Essawy; Saad R. Abdel Wahed; Motasem M. Alredy; Ahlam M. Ismail; Gehan L. Abdel Hakeem; Khaled F. Riad (The Egyptian Journal of Radiology and Nuclear Medicine, 2016)
Objective: To assess the utility of 64 MDCT in the diagnosis, staging and follow-up of HB patients. Patients & methods: This study included 17 children, 9 males and 8 females with HB from multiple centers aged 6 months- 3 years. Patients were subjected to complete clinical examination and laboratory investigations at presentation and during follow-up. Patients were evaluated, staged and treated according to SIOPEL HB protocols for management. Imaging evaluation was conducted using abdominal U/S, bone scan and MDCT for chest and abdomen. Results: All patients were presented with abdominal mass and elevated AFP level, Jaundice seen in only 1 patient. On MDCT, 13 patients had single focal lesion, 2 patients had multiple foci and 2 patients showed diffuse disease. MDCT was more accurate than US in detecting site, multiplicity, density and lymph nodes (LNs). Regarding tumor staging, MDCT findings were confirmed surgically. In follow-up of patients MDCT was detected with accuracy residual or recurrent lesions in 3 cases. Conclusion: MDCT in children with HB accurately displayed the extent of hepatic involvement by tumor, tumor staging and its proximity to vascular structures that help the surgeon to identify the tumor resectability and can be used in follow-up.